The People's Republic of China : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper reviews China's progress along various dimensions of rebalancing. External rebalancing has advanced well, while progress on internal rebalancing has been mixed-substantial on the supply side, moderate on the demand side, and limited on credit dependence. Rebalancing on the environment and inclusiveness has lagged. The high national rate of saving is expected to fall owing to demographic change and a stronger social safety net. The consumption ratio is expected to increase with a rising labor income share and less household saving. Supply-side rebalancing from industry to services is expected to advance further, helping reduce the carbon intensity of output and promote income equality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet